2020
DOI: 10.1136/jech-2019-213056
|View full text |Cite
|
Sign up to set email alerts
|

Is socioeconomic position associated with bronchiolitis seasonality? A cohort study

Abstract: BackgroundUnderstanding differences in the seasonality of bronchiolitis can help to plan the timing of interventions. We quantified the extent to which seasonality in hospital admissions for bronchiolitis is modified by socioeconomic position.MethodsUsing Hospital Episode Statistics, we followed 3 717 329 infants born in English National Health Service hospitals between 2011 and 2016 for 1 year. We calculated the proportion of all infant admissions due to bronchiolitis and the incidence rate of bronchiolitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Three studies in the UK produced similar findings, with a peak in admissions seen in infants born during the winter months of September to December [ 7 , 15 , 16 ]. R eeves et al .…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Three studies in the UK produced similar findings, with a peak in admissions seen in infants born during the winter months of September to December [ 7 , 15 , 16 ]. R eeves et al .…”
Section: Resultsmentioning
confidence: 62%
“…L ewis et al . (2020) [ 16 ] documented the increased bronchiolitis admission rate in England from 47.4 (95% CI 46.8–47.9) to 58.9 per 1000 infant-years (95% CI 58.3–59.5) between 2012 and 2016. A study by T umba et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PICNIC study population includes two national birth cohorts comprising all children born in England between 2005 and 2014 inclusive and in Scotland between 1997 and 2020 inclusive. Children will be followed from the discharge date of their postnatal admission until their date of death, migration out of Scotland or England (defined using the methods described in Hardelid et al 6 for Scotland and Lewis et al 2 for England), or their fifth birthday, whichever occurs first, via hospital admission and death records. The Scottish birth cohort will also include longitudinal data on community dispensed drugs, microbiology test results, vaccination and health visiting (see the following sections).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…1 RTI admission rates peak in winter months, contributing to the ‘winter crisis’ in the National Health Service (NHS). 2 Severe RTI symptoms in infancy and early childhood have been linked to adverse respiratory health outcomes in later childhood, including asthma. 3 We have previously shown that 79% of annual admissions for RTIs in infants <1 year old can be attributed to respiratory syncytial virus (RSV) and other viral infections for which no vaccines are currently available.…”
Section: Introductionmentioning
confidence: 99%